Factors Affecting Indonesian University Students’ Participation in Synchronous vs Asynchronous Online English Classess: A Perceptual Analysis - Saputra, Nizar; Mulyani; Asirah (JET (Journal of English Teaching), 2024)
With the expanding realm of online education in Indonesia, determining factors influencing university students' participation in distinct modes of virtual learning is crucial to developing more effective digital pedagogy. This research aims to scrutinize factors affecting Indonesian EFL (English as a Foreign Language) university students' low participation in synchronous and asynchronous online learning classes. This research was framed quantitatively by employing a five-rating Likert-scale survey. This survey aimed to illuminate the underlying factors that shape students' behaviors or perceptions within these online learning modes. The findings showed that factors affecting the Indonesian tertiary EFL students' low participation in synchronous virtual learning mode include technical problems, learning anxiety, social isolation, socioeconomic status, and pet and human interferences. Meanwhile, heavy workloads, tedious content, and deprivation of human contact were associated with the factors affecting the EFL students' low participation in asynchronous learning modes.